Yankee yarns : storytelling and the invention of the national body in nineteenth-century American culture - Schäfer, Stefanie, Dr.; Schäfer, Stefanie (Edinburgh : Edinburgh University Press, 2021)
A systematic study of the most iconic national character in the US in nineteenth-century literature and culture.
An Ambiguous National Character -- The Yankee and Transatlantic Nationalism: Aims and Scope of this Study -- Whiteness, Manhood, and the Body Politic -- Literary Fraudulence, Activist Readership, and the Economy of Storytelling -- Chapters and Coda -- 1. John Bull and Brother Jonathan: A Transatlantic Affair -- From Allegory to Character: John Bull in Early British National Iconography -- Transatlantic Kinship in Nineteenth-Century U.S. Print Culture: Between National Literature and Imperial Fantasy -- The National Body as Image and Text: Thomas Nast's Uncle Sam and Humor Magazines -- 2. Theater of/for the Nation: The Stage Yankee as Metatheatric Sign -- Yankee Theater and Drama Scholarship -- Tales of Country and City: From Jonathan to Uncle Nat -- The Stage Yankee at Large: International Projections and Yankee Ambiguity -- 3. The Yankee Peddler Conjures an American Marketplace -- Monster, Wizard, Founding Father: The Yankee Peddler in Cultural and Economic Historiography -- The Secrets of the Yankee Peddler in Nineteenth-Century Literature -- Yankee Clocks and Wooden Nutmegs: "Yankee Notions" and the Making of a National Marketplace -- 4. New England's "Homespun Yankee" in the Cultural and Literary Imagination -- Fantasies of New England in Regional Historiography -- The Yankee Schoolmaster as American Educator -- "The Season of Youth for Nations and Individuals": New England Villages and Yankee Character -- John Neal's Down-Easters: Whittling, Storytelling Yankees -- Yankee Homespun -- 5. Yankee Politics: A Coda.
Includes bibliographical references (pages 277-300) and index.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: American literature -- 19th century -- History and criticism; National characteristics, American, in literature; Americans in literature; Popular culture -- United States -- History -- 19th century; Littérature américaine -- 19e siècle -- Histoire et critique; Culture populaire -- États-Unis -- Histoire -- 19e siècle.; LITERARY CRITICISM / American / General; American literature; Americans in literature; National characteristics, American, in literature; Popular culture; United States; 1800-1899; Criticism, interpretation, etc; History